Prevalence of Transfusion-transmissible Infections in Blood Donors: A Private Hospital Experience - Henry Rantai, Gudum; Chrisdyana Anjali, Sirucoh; Nur Amirah, Rukyno; Saruveish, Mogan; Tay, Siow Phing (Fakulti Perubatan dan Sains Kesihatan, UPM, 2024)
Introduction: Blood transfusion, a vital component of established medical protocols, has the potential to save lives and enhance well-being. Nonetheless, it carries inherent risks, with transfusion-transmissible infections (TTIs) remaining a global public health concern. Vigilant monitoring of TTI prevalence among blood donors and understanding of evolving patterns are crucial safety endeavours. The objective of this study was to assess the prevalence of TTIs and their patterns among blood donors within a private hospital’s transfusion service. Methods: This retrospective study involved TTI testing results of blood donations at Normah Medical Specialist Centre (NMSC) in Kuching, Sarawak, spanning a decade from 2010 to 2019. Results: A total of 7329 blood donors contributed 16,085 blood units (2010 – 2019). Among them, 353 donors exhibited reactivity to TTIs, resulting in a prevalence of 4.81%. The majority of reactive donors were male (87.3%), of Malay ethnicity (62.6%), and first-time donors (73.9%). The prevalence rates were highest for HCV (2.69%), followed by HBV (1.41%), HIV (0.42%), and syphilis (0.39%). Both HBV and HCV demonstrated declining prevalence trends, while the prevalence of HIV and syphilis remained consistently low. The response to notification of positivity among reactive donors stood at a mere 4.0%, and the seroconversion rate among repeat donors was 4.6%. No significant disparities in prevalence or response rates were observed between first-time and repeat donors. Conclusions: The prevalence of TTIs within NMSC’s blood donor populace remains relatively low, though not negligible. The responsiveness of reactive donors to notifications displayed considerable deficiencies.